The Effect of Profitability, Firm Age, and The Independent Board of Commissioners to Corporate Social Responsibility Disclosure Listed on IDX - L, Lasonia Luxeya (Jurnal KIAFE, 2021)
THE EFFECT OF PROFITABILITY, FIRM AGE, AND THE INDEPENDENT BOARD OF COMMISSIONERS TO CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE LISTED ON IDXBy:Lasonia Luxerya LamonggaB1034171022Faculty of Economic and BusinessTanjungpura UniversityABSTRACTThis research was conducted to find out how the influence of profitability, firm age, and the independent board of commissioners to corporate social responsibility disclosure listed on the Indonesia Stock Exchange in 2015 "“ 2019. The research conducted is quantitative research and the data source used in this study is secondary data in the form of annual reports of related companies. The samples in this research consist of 37 mining companies with data analysis method in the form of descriptive statistics test, classic assumption test, and multiple linear regressions. This research used corporate social responsibility disclosure as dependent variable, while independent variables used are profitability, firm age, and the independent board of commissioners. The result of this research showed that there is a significant influence of variable profitability on corporate social responsibility. While, variable firm age and the independent board of commissioners does not have a significant influence on corporate social responsibility.Keywords: Profitability, Firm Age, The Independent Board of Commissioners, Corporate Social Responsibility Disclosure.ReferencesBarnas, A. N., Hapsari, D. W., & Yudowati, S. P. (2016). Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (Studi Empiris Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014). E-Proceeding Of Management,3(2), 1566-1571.Brown, N., & Deegan, C. (1998). The Public Disclosure of Environmental Performance Information--a Dual Test of Media Agenda Setting Theory and Legitimacy Theory. Accounting and Business: Research 29 (1): 21-41.Dewi, N., & Sari, M. (2019). Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas pada CSR Disclosure. E-Jurnal Akuntansi Universitas Udayana, 27, 1956-1982.Hadi, N. (2011). Corporate Social Responsibility. Yogyakarta: Graha Ilmu.Indraswari, G., & Astika, I. (2015). Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Saham Publik Terhadap Pengungkapan CSR. E-Jurnal Akuntansi Universitas Udayana 1, 450, 3-451. Retrieved from https://doi.org/10.1136/annrheumdis-2017-eular.3008.Kasmir. (2017). Analisis Laporan Keuangan. Jakarta: Grasindo.Manurung, R. (2008). "Haram" Hukumnya Terima CSR dari Corporate Perusak. Yogyakarta: Graha Ilmu.Mardikanto, R. (2018). Corporate Social Responsibility. Bandung: Alfabeta.Ratnasari, Y., & Prastiwi, A. (2010). Pengaruh Corporate Governance Terhadap Luas Pengungkapan Social Responsibility di Dalam Sustainability Report. Bandung: Universitas Dipenogoro.Sembiring, E. R. (2005). Karakteristik Perusahaan dan Pengungkapan Tanggung Jawab Sosial (Studi Empiris Pada Perusahaan yang Tercatat di Bursa Efek Indonesia). Jurnal Simposium Nasional Akuntansi Vol. 8, 379-395.Setiawati, E. Z., & Artha, R. (2013). Pengaruh Karakteristik Perusahaan Terhadap CSR (Survey pada Industri Perbankan di Indonesia). Proceeding Seminar Nasional Dan Call for Papers Sancall 2013, 168-188.Sudaryono, B. (2007, Agustus). Kajian atas Faktor-Faktor yang Mempengaruhi Pengungkapan Lingkungan (Environmental Disclosure) Pada Perusahaan Publik di BEJ Pada Tahun 2004-2005. Media Riset Akuntansi, Auditing dan Informasi, Vol 7, No 2, Agustus, 107-139.Sugiyono. (2015). Metode Penelitian Bisnis (Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta.Sumaryono, A., & Asyik, N. F. (2017). Pengaruh Size, Profitabilitas, dan Leverage terhadap Pengungkapan Corporate Social Responsibility. Jurnal Ilmu Dan Riset Akuntansi, 6, 1-17.Untari, L. (2010). Effect on Company Characteristics Corporate Social Responsibility Disclosure in Corporate Annual Report of Consumption Listed in Indonesia Stock Exchange. Jakarta: Universitas Gunadarma.Utami, S., & Prastiti, S. D. (2011). Pengaruh Karakteristik Perusahaan Terdadap Social Disclosure. Jurnal Ekonomi Bisnis. Tahun 18. No. 1. Maret, 63-69.